Differential effects of intermittent energy restriction vs. continuous energy restriction combined high-intensity interval training on overweight/obese adults: A randomized controlled trial - Xu, Rui; Cao, You-Xiang; Chen, Yu-Ting; Jia, Yu-Qi (Frontiers in Nutrition, 2022)
Objective: Intermittent energy restriction (IER) or continuous energy restriction (CER) can lead to weight loss, but always accompanied with reduced health fitness. Whether IER or CER combined with high intensity interval training (HIIT) can effectively eliminate the negative effect still unknow. This study aims to evaluate the different effects of IER or CER combined with HIIT on health fitness in overweight/obese adults. Methods: Fifty-seven overweight/obese adults were randomly assigned to iER (IER+HIIT), cER(CER+HIIT), or ND (normal-diet+HIIT) group. iER consumed 30% energy needs on 2 nonconsecutive days/week, and 100% for another 5 days; CER consumed 70% of energy needs; ND consumed 100% of energy needs. All groups completed 4-week HIIT intervention (3min bouts at 80%V(•)O2max separated by 3min 50%V(•)O2max recovery, 30 min/training sessions, 5 sessions/week). Body composition, body circumference, fasting blood lipids and cardiorespiratory fitness (CRF) were measured pre- and post-intervention. Results: After 4-week intervention, iER tends to be superior than cER in the improvement of health fitness. The mean body weight loss was 4.57 kg (95% confidence interval [CI], 4.1 to 5.0, p＜0.001) in iER and 2.46 kg (95% CI, 4.1 to 5.0, p＜0.001) in cER. Results of analyses of body fat percentage (BF%), waist circumference (WC), hip circumference (HC) were consistent with the results of the primary outcome. In addition, fasting blood lipids and CRF improved after intervention but without significant changes (p >0.05). Conclusion: Both iER and cER could effective in weight loss and increased CRF, and iER seems more effective than cER for eliminate the negative effect.